Injectable In Situ-Forming Hydrogels for Protein and Peptide Delivery - Park, Seung Hun; Ji, Yun Bae; Park, Joon Yeong; Ju, Hyeon Jin; Lee, Mijeong; Lee, Surha; Kim, Jae Ho; Min, Byoung Hyun; Kim, Moon Suk (Advances in Experimental Medicine and Biology, 2020)
Injectable in situ-forming hydrogels have been used clinically in diverse biomedical applications. These hydrogels have distinct advantages such as easy management and minimal invasiveness. The hydrogels are aqueous formulations, and a simple injection at the target site replaces a traditional surgical procedure. Here, we review injectable in situ-forming hydrogels that are formulated by physical and chemical methods to deliver proteins and peptides. Prospects for using in situ-forming hydrogels for several specific applications are also discussed.
Keywords: Drug Delivery Systems; Humans; Hydrogels; Injections; Peptides; Proteins; Biomedical application of hydrogel; Click reaction; Covalent and non-covalent bonding; Crosslinking; Drug delivery system; Drug depot; Electrostatic interaction; Injectable in situ forming hydrogels; Physical interaction; Protein and peptide; Protein and peptide loading